STUDY OF MURAL ART STYLE IN PUBLIC SPACES OF THE HYSTERIA COMMUNITY IN SEMARANG - Hermalita Siwi, Vini (Universitas Negeri Semarang, 2025)
This study aims to analyze the style, values, meaning, and educational function of the mural works of the Hysteria Community in public spaces in the city of Semarang, while also examining the public's acceptance of the social messages conveyed through these murals. A qualitative approach was used through observation, interviews, and documentation of two major works: